2021
DOI: 10.3390/polym13203537
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Regeneration Mechanism of β-Sheet Silk Fibroin in a Rat Burn Wound Healing Model

Abstract: Therapeutic dressings to enhance burn wound repair and regeneration are required. Silk fibroin (SF), a natural protein, induces cell migration and serves as a biomaterial in various dressings. SF dressings usually contain α-helices and β-sheets. The former has been confirmed to improve cell proliferation and migration, but the wound healing effect and related mechanisms of β-sheet SF remain unclear. We investigated the effects of β-sheet SF in vivo and in vitro. Alcohol-treated α-helix SF transformed into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 84 publications
1
9
0
Order By: Relevance
“…In vitro studies have demonstrated amyloid could stimulate cells to produce multiple cytokines and chemokines and induce cell migration through integrin‐ρ‐GTPase linked signalling (Connolly et al, 2011). Moreover, the β‐sheet structure of amyloid was also shown to enhance the motility of cells by increasing the expression of matrix metalloproteinase‐12 and integrin β1 (Chou et al, 2021). The positive effects of PTL on cell migration might partly attributed to these regulatory pathways involved as well as the upregulation of chemokines molecules such as integrin β1, on the other hand, the amyloid structure in PTL could capture proteins and other molecules, which create high concentrations of nutrients nearby and thus contribute to recruiting HDPCs.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have demonstrated amyloid could stimulate cells to produce multiple cytokines and chemokines and induce cell migration through integrin‐ρ‐GTPase linked signalling (Connolly et al, 2011). Moreover, the β‐sheet structure of amyloid was also shown to enhance the motility of cells by increasing the expression of matrix metalloproteinase‐12 and integrin β1 (Chou et al, 2021). The positive effects of PTL on cell migration might partly attributed to these regulatory pathways involved as well as the upregulation of chemokines molecules such as integrin β1, on the other hand, the amyloid structure in PTL could capture proteins and other molecules, which create high concentrations of nutrients nearby and thus contribute to recruiting HDPCs.…”
Section: Discussionmentioning
confidence: 99%
“…The 3T3 cells deposited collagens I and IV in an open mesh-like pattern, while HDFs deposited these collagens as densely aligned strands that, in places, were crossed-linked. Interestingly, others found that dressings of lyophilized SF in a β-sheet form following ethanol treatment caused increased HDF migration and promoted the expression by HDFs of the ECM proteins, fibronectin, and collagen III [ 65 ]. Collagens I and IV and fibronectin are key ECM components of skin [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…43 Another study reported that the in vivo application of SF (in β-sheet form) to burn wounds promoted the expression of MMP-12, fibronectin, integrin-β1, and type III collagen in the granulation tissue. 46 Moreover, SF promoted the upregulation of three distinct pathways: phosphoinositide 3-kinase (PI3K/ AKT), mitogen-activated protein kinase kinase (MEK1), and c-Jun N-terminal kinase (JNK) resulting in the activation of induced c-Jun expression through downstream mechanisms and cell migration. Aykac et al reported that SF has a protective effect in a burn wound (rat model) by stimulating the apoptotic pathway.…”
Section: Silk Fibroin For Wound Care Applicationsmentioning
confidence: 99%